Humboldt, Historismus, Humboldteanisierung. Der „Geschichtsschreiber von Amerika“, die Massensklaverei und die Globalisierungen der Welt. (Fortsetzung von HiN 3) - Zeuske, Michael (HiN - Alexander von Humboldt im Netz. Internationale Zeitschrift für Humboldt-Studien, 2021)
AbstractThis article treats Alexander von Humboldt as an Atlantic intellectual, not only as an european intellectual. The article tries to analize also the „Ensayo político sobre la Isla de Cuba“ as a key text of the second globalization („industrial revolution“). Against the background of our knowledge about the reality at the beginnings of the 19th century the article analizes the humboldtian presentation of this reality during his stay in Cuba (1801/1804), confronting it with his „Essay“ about Cuba (1826-1831), as well tries to demonstrate the position of Humboldt in the historical thinking. The third part explains the relations of Humboldt to the network of Cuban intellectuals and with some important personalities of the Cuban elite (Arango, Calvo) in the development of his work. ResumenEl artículo trata Humboldt como intelectual atlántico, no solo como intelectual europeo. Trata de analizar también el „Ensayo político sobre la Isla de Cuba“ como texto clave de la segunda globalización („revolución industrial“). Bajo el trasfondo de los conocimientos de nosotros sobre la realidad de aquel entonces analiza la presentación humboldtiana de esta realidad durante su estancia en Cuba (1801/1804) y en el „Ensayo“ sobre Cuba (1826-1831), así como la posición de Humboldt en el pensamiento histórico. Una tercera parte trata de explicar las relaciones de Humboldt con la red de intelectuales cubanos y con varias personas (Arango, Calvo) en el desarrollo de su obra.